UJI KELAYAKAN BUKU AJAR SENI BERBASIS KEARIFAN LOKAL KABUPATEN JOMBANG (RELEVANSI DALAM PENGUATAN KARAKTER MAHASISWA PGSD UNIVERSITAS HASYIM ASY’ARI TEBUIRENG JOMBANG) - Ratih Asmarani; Novia Dwi Rahmawati; Sri Widoyoningrum (Primary: Jurnal Pendidikan Guru Sekolah Dasar, 2020)
The development of learning resources such as the art textbook based on local wisdom in Kabupaten Jombang was conducted by referring to the Borg dan Gall model. After that, media experts, material experts,and the students examined its feasibility. The aim of this study was to investigate the feasibility of the art textbooks based on local wisdom in Kabupaten Jombang from some expert views. This study employed a descriptive qualitative research method.The data were collected by using participatory observation methods and the field trials in order to determine the usefulness of the product. The data from the expert validations and students were analyzed by using the Likert scale calculation criteria. After that, the data were analyzed by converting the total score of the test results into a percentage form. Then, it was converted into qualitative data by using the product feasibility score interpretation guidelines. The data were used as a reference for product improvement. The average score obtained from material experts were 77%; the score from media experts was 95%;and the result of trial for the large group of students was 85.3%. Finally, the overall average score was 86.47%. Based on the score interpretation, the product was in a very suitable category to be used as the main learning resource.